La sustancia: capitalismo, salud, corporalidad y régimen neoliberal - Araya-Vargas, Sebastián Alberto (2025)
In this review of the film La sustancia (2024), I analyze several key moments in the film based on contributions from the anthropology of the body and health.First, I examine the relationship between the protagonist and her boss as a dynamic inherited from the early days of capitalism. Next, I explore how the film shows that the demands of capital affect the definition of a healthy body, which is determined by factors such as youth, beauty, and productivity. Finally, I offer an interpretation of the meaning of “the substance” within the context of the contemporary neoliberal regime.